Protective mechanisms of Zanthoxylum bungeanum essential oil on DSS-induced ulcerative colitis in mice based on a colonic mucosal transcriptomic approach. Issue 18 (7th September 2022) - Zhang, Huan; Guo, Zhiqing; Wang, Xiao; Xian, Jing; Zou, Liang; Zheng, Chuan; Zhang, Jinming
Abstract : The ameliorative effects on ulcerative colitis (UC) as well as the related mechanisms of the essential oil derived from the edible herb Zanthoxylum bungeanum Maxim (ZBEO) have been demonstrated herein. Abstract : The ameliorative effects on ulcerative colitis (UC) as well as the related mechanisms of the essential oil derived from the edible herb Zanthoxylum bungeanum Maxim (ZBEO) have been demonstrated herein. Based on GC-MS analysis, 45 volatile compounds in ZBEO were determined for its quality control. In vitro studies showed that after pretreatment with ZBEO, the disordered expression levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) and an anti-inflammatory cytokine (IL-10) on colon epithelial NCM460 cells induced by lipopolysaccharide (LPS) could be reversed. Additionally, oral administration of ZBEO significantly alleviated colitis in dextran sulfate sodium (DSS)-induced UC mice, including body weight loss, colon length shortening, disease activity index and colonic pathological damage. Furthermore, to uncover the anti-UC mechanisms of ZBEO, analysis of transcriptomes by next-generation sequencing technology was performed to explore the RNA genetic variation on colon tissues. Based on GO analysis and KEGG pathway analysis, a series of genetic pathways involved in the protective role of ZBEO against UC were determined. As a result, ZBEO treatment could decrease the expression of VCAM-1, TLR8, IL-1β and IL-11 mRNA as verified by qRT-PCR, which are involved in these potential genetic pathways. In conclusion, ZBEO administration would be a medicinal or dietary supplementation strategy for ulcerative colitis treatment.